Properties of the hard-sphere fluid at a planar wall using virial series and molecular-dynamics simulation - Paganini, Iván Eduardo (2018)
We study the hard-sphere fluid in contact with a planar hard wall. By combining the inhomogeneous virial series with simulation results, we achieve a new benchmark of accuracy for the calculation of surface thermodynamics properties such as surface adsorption Γ and the surface free energy (or surface tension), γ. We briefly introduce the problem of choosing a position for the dividing surface and avoid it by proposing the use of alternative functions to Γ and γ that are independent of the adopted frame of reference. Finally, we present analytic expressions for the dependence of system surface thermodynamic properties on packing fraction, ensuring the high accuracy of the parameterized functions for any frame of reference. The proposed parametric expressions for both, Γ and γ, fit the accurate simulation results within the statistical error.